Lithium composite negative electrode and preparation method and application thereof
By using the composite structure of porous resin layers, lithium -friendly coating and metal lithium layer in the negative electrodes of lithium batteries, the problem of lithium composite negative materials in volume expansion, lithium -branch crystal growth and interface side effects, realized high -quality energy The density and mechanical strength are improved, and it is compatible with the existing lithium battery preparation process.
Patent Information
- Application Number
- CN202310924386.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
AI Technical Summary
The existing lithium composite anode materials have problems in volume expansion, lithium dendrites growth and interface side reactions, and are difficult to compatible with the existing lithium battery preparation process, resulting in insufficient energy density and mechanical strength.
The porous resin layer is used as the main osteogenesis structure, combined with the lithium coating and the metal lithium layer, to achieve compound through the method of mechanical roller pressing, and regulate the mutual embedded thickness of the porous resin layer and the metal lithium layer density.
Effectively alleviate the volume expansion and lithium -branch crystal growth in the process of lithium deposition, improve the mechanical strength and energy density, and compatible with the existing lithium -ion battery negative production and preparation process, and achieve roll -to -roll production.
Smart Images

Figure BDA0004359672900000081 
Figure HDA0004359672910000011 
Figure HDA0004359672910000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery negative electrodes, and in particular to a lithium composite negative electrode and a preparation method and application thereof. Background Art
[0002] Metallic lithium has a high mass energy density (3860mAh / g) and a low potential for lithium. It is a candidate for the next generation of high-energy-density batteries and an important lithium supplement material. However, directly using metallic lithium as the negative electrode material of the battery is prone to problems such as large volume expansion, severe lithium dendrite growth, and poor stability and safety. In the prior art, some researchers use carbon paper, carbon cloth, etc. as the skeleton structure, and use a hot melt method to composite metallic lithium with carbon paper, carbon cloth, and fiber to obtain a lithium composite negative electrode. However, the obtained lithium composite negative electrode is not compatible with the existing lithium battery preparation process. First, carbon paper, carbon cloth, etc. have poor mechanical strength, and it is difficult to leave an effective pole ear position, so it is very difficult to make soft-pack, cylindrical and other batteries; second, the obtained lithium composite negative electrode cannot effectively inhibit volume expansion. Lithium tends to deposit on the top layer of the lithium composite negative electrode during the deposition process, and the probability of deposition inside the structure is low; third, the actual mass energy density of the lithium composite negative electrode is low. The existing technology uses carbon paper, carbon cloth and fiber to modify the lithium metal negative electrode, but due to the limitations of the existing process technology and the thickness of the lithium negative electrode, the existing technology can only achieve a minimum thickness of carbon paper, carbon cloth and fiber of not less than 100μm on the basis of not being able to infinitely increase the thickness of the lithium negative electrode. The increase in the thickness of carbon paper, carbon cloth and fiber will inevitably affect the decrease in the mass ratio and volume ratio of metal lithium in the lithium composite negative electrode, resulting in a very low actual effective energy density of the lithium composite negative electrode, and the relationship between energy density and lithium negative electrode thickness cannot be solved. Summary of the invention
[0003] The present invention aims at the problems in the prior art and discloses a lithium composite layer. The lithium composite layer of the present invention is used for the negative electrode sheet to obtain a lithium composite negative electrode. The lithium composite negative electrode can effectively alleviate the problems of large volume expansion, severe lithium dendrite growth, and many interface side reactions during the deposition and dissolution of metal lithium. The lithium composite negative electrode obtained by the present invention has a smaller thickness and can also achieve high quality energy density, high volume energy density, and higher mechanical strength. In addition, the lithium composite negative electrode of the present invention can directly use the existing lithium ion battery negative electrode production and preparation process, and can achieve roll-to-roll production.
[0004] The present invention is achieved through the following technical solutions:
[0005] The present invention provides a lithium composite layer, which comprises a lithium-philic coating, a porous resin layer and a metal lithium layer which are sequentially arranged near a current collector side.
[0006] More preferably, the metal lithium layer is partially embedded in the porous resin layer.
[0007] The above-mentioned design of the present invention, the lithium composite layer obtained by the present invention is used for the lithium composite negative electrode obtained by the negative electrode sheet, and the lithium composite negative electrode has better energy density and mechanical strength on the basis of adjustable thickness, and the lithium composite negative electrode can also realize the uniform deposition of metal lithium from the surface of the lithium composite negative electrode to the bottom layer of the lithium composite negative electrode, thereby reducing the volume expansion of the negative electrode. Specifically, by designing a porous resin layer as the main skeleton structure of the lithium composite negative electrode, the porous resin layer has a good ability to store metal lithium, and the porous resin layer can effectively accommodate the metal lithium deposited from the positive electrode to the negative electrode, thereby reducing the volume expansion of the negative electrode. On this basis, the lithium-philic coating can change the deposition order of metal lithium, and the bottom lithium-philic coating can induce the metal lithium deposited in the porous resin layer to further begin to uniformly deposit upward toward the bottom layer of the lithium composite negative electrode, and the use of the lithium-philic coating can change the deposition morphology of metal lithium, induce the uniform and dense deposition of metal lithium, and the uniform and dense deposition of metal lithium is conducive to reducing interface side reactions and improving the cycle stability of the battery. A metallic lithium layer is arranged on the porous resin layer. Firstly, the porous resin layer and the metallic lithium layer have good compatibility, and a good composite effect can be obtained by mechanical rolling. Secondly, part of the metallic lithium layer is embedded in the porous resin layer, which is beneficial for the smooth deposition of metallic lithium into the porous resin layer on the one hand, and on the other hand, the mutual embedding thickness of the porous resin layer and the metallic lithium layer can be adjusted to control the total thickness of the lithium composite negative electrode. In addition, the porous resin layer also has space for lithium deposition, which is beneficial to reduce the volume expansion of the negative electrode. In addition, the mutual embedding method can increase the mass ratio and volume ratio of the metallic lithium layer in the lithium composite negative electrode, which is beneficial to improve the energy density of the battery. A current collector can also be arranged under the lithium-philic coating to improve the mechanical strength of the lithium composite negative electrode.
[0008] As a further solution, the raw material of the porous resin layer includes trialdehyde resin, the porosity of the raw material is 60%-90%, and the specific surface area is 10m 2 / g-300m 2 / g, pore size is 1nm-500nm. First, trialdehyde resin can improve the flexibility of lithium composite negative electrode and is suitable for different battery processes; second, the pore size, porosity and specific surface area of trialdehyde resin are further designed, so that trialdehyde resin further improves the absorption, which is conducive to the embedding of metal lithium layer into the porous resin layer formed by trialdehyde resin. The larger porosity provides sufficient space for the deposition of metal lithium, while reducing the mass ratio of resin material, which is conducive to improving energy density. The appropriate specific surface area provides sufficient surface for the deposition of metal lithium in the resin pores, and the appropriate pore size is conducive to the rapid conduction of lithium ions therein. Third, because trialdehyde resin has sponge-like elasticity, and trialdehyde resin and metal lithium layer have better compatibility, the metal lithium layer can be well compounded into the porous resin layer by simple mechanical rolling and other methods, which is conducive to forming a well-integrated composite structure, so that the metal lithium in the lithium composite negative electrode can be smoothly and evenly deposited from the surface of the metal lithium layer to the direction of the lithium-philic coating. Based on the above reasons, the present invention needs to limit the porosity, specific surface area and pore size of the raw materials of the porous resin layer; the porosity is between 60% and 90%, and the specific selection can be 60%, 65%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88% and 90%; the specific surface area is 10m 2 / g-300m 2 / g, the specific choice can be 10m 2 / g, 30m 2 / g, 50m 2 / g, 70m 2 / g, 85m 2 / g, 90m 2 / g, 95m 2 / g、100m 2 / g、105m 2 / g, 110m 2 / g, 115m 2 / g, 120m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g、300m 2 / g; the pore size is between 1nm-500nm, and the specific selection can be 1nm, 10nm, 15nm, 18nm, 20nm, 22nm, 24nm, 26nm, 28nm, 30nm, 32nm, 35nm, 40nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm.
[0009] As a further solution, the particle size of the raw material of the porous resin layer ranges from 3μm to 100μm. Reasonable particle size design can take into account both energy density and power density. If the particle size of the resin material is too large, the thickness of the coating layer will be too large, which will reduce the energy density of the composite negative electrode layer. If the particle size of the resin material is too small, the conductivity of lithium ions therein will be reduced, which will inhibit the effective deposition of metallic lithium in the porous resin layer and increase the volume expansion. The porous resin layer is conducive to the formation of channels for the deposition of metallic lithium. The porous resin layer acts as a bridge to facilitate the smooth deposition of metallic lithium from the metallic lithium layer to the underlying lithium-philic coating. Based on the above reasons, the particle size of the raw material of the porous resin layer needs to be limited to between 3μm and 100μm in the present invention, and the specific selection can be 3μm, 10μm, 25μm, 35μm, 50μm, 58μm, 75μm, 95μm, and 100μm.
[0010] As a further solution, the trialdehyde resin includes one or more of urea-formaldehyde resin glue, phenolic resin glue, and melamine resin glue. Phenolic resin glue has better absorption capacity, chemical stability, corrosion resistance, aging resistance, and heat resistance, and is more conducive to being used in batteries to promote stable electrical performance of the batteries.
[0011] As a further solution, the lithium-philic coating is a composite material of a lithium-philic material and a carbon material; the raw materials of the lithium-philic coating include a lithium-philic material and a carbon material, and the lithium-philic material is uniformly dispersed and coated on the surface of the carbon material.
[0012] As a further solution, the lithium-philic material can form an infinite solid solution with metallic lithium. The lithium-philic material and the carbon material form a lithium-philic nanocomposite material with good lithium-philic ability, and the lithium-philic coating formed by the lithium-philic nanocomposite material can form an infinite solid solution with the deposited metallic lithium, thereby changing the deposition morphology of metallic lithium and inducing uniform and dense deposition of metallic lithium.
[0013] As a further solution, the mass ratio of the carbon material to the lithium-philic material is (10-1000):1.
[0014] As a further solution, the particle size range of the carbon material is 10nm-500nm; the particle size range of the lithium-philic material is 1nm-10nm. The lithium-philic material can be evenly coated on the surface of the carbon material, thereby obtaining a thin, uniform and flat lithium-philic coating, further promoting the formation of uniform and dense deposition of metallic lithium. Carbon materials with suitable particle sizes have higher electron conduction capabilities, which are conducive to the rapid conduction of electrons. Nano-sized lithium-philic materials are conducive to further enhancing the lithium-philic properties of nano-lithium-philic composite materials, and are conducive to inducing rapid and preferential deposition of metallic lithium thereon. Based on the above reasons, the particle size range of the carbon material and the particle size range of the lithium-philic material need to be limited in the present invention, wherein the particle size range of the carbon material is 10nm-500nm, and the specific selection can be 10nm, 20nm, 30nm, 35nm, 38nm, 40nm, 42nm, 44nm, 46nm, 50nm, 52nm, 54nm, 56nm, 60nm, 62nm, 65nm, 70nm, 100nm, 200nm, 300nm, 400nm, 500nm; the particle size range of the lithium-philic material is 1nm-10nm, and the specific selection can be 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm.
[0015] As a further solution, the lithium-philic material includes one or more of silver, magnesium, and zinc. The silver, magnesium, zinc and other elements as lithium-philic materials can react with metallic lithium to form an infinite solid solution, ensuring that the metallic lithium deposition behavior can be effectively regulated under long-cycle conditions, while gold, silicon and other elements can induce metallic lithium deposition under certain conditions, but can only form an alloy phase with metallic lithium, and cannot form a continuous solid solution. After a certain number of cycles, they will lose their effective regulation effect on metallic lithium.
[0016] As a further solution, the carbon material includes one or more of conductive carbon (Super-P), acetylene black, graphene, single-arm carbon nanotubes, and multi-arm carbon nanotubes.
[0017] As a further solution, the raw material of the porous resin layer includes phenolic resin glue, the porosity is 70%-90%, and the specific surface area is 90m 2 / g-110m 2 / g, pore size is 20nm-30nm; the particle size range of the carbon material in the lithium-philic coating is 40nm-60nm; the lithium-philic material in the lithium-philic coating is silver, and the particle size range of the silver is 4nm-6nm. The physical properties of suitable porous resin materials are conducive to taking into account both energy density and power density. The selection and design of suitable lithium-philic materials and the design coordination of carbon materials are conducive to inducing rapid and preferential deposition and dissolution of metallic lithium thereon, thereby reducing volume expansion. By designing the above parameters, the expansion rate of the lithium composite negative electrode of the present invention is significantly reduced.
[0018] As a further solution, the thickness of the lithium-philic coating is 1 μm-10 μm, the thickness of the porous resin layer is 5 μm-200 μm, and the thickness of the metal lithium layer is 1 μm-200 μm.
[0019] As a further solution, the raw material of the lithium-philic coating also includes a binder.
[0020] As a further solution, the binder accounts for 1%-40% by mass of the raw materials of the lithium-philic coating.
[0021] As a further solution, the raw material of the porous resin layer further includes a binder and a conductive agent.
[0022] As a further solution, the binder accounts for 1%-10% by mass in the raw materials of the porous resin layer; and the conductive agent accounts for 1%-10% by mass in the porous resin layer.
[0023] As a further solution, the binder includes one or more of PVDF (polyvinylidene fluoride), aqueous dispersion of LA133-acrylonitrile copolymer, PTFE (polytetrafluoroethylene), PAN (polyacrylonitrile), CMC (carboxymethyl cellulose), and SBR (styrene-butadiene rubber).
[0024] As a further solution, the conductive agent includes one or more of conductive carbon, graphene, single-arm carbon nanotubes, and multi-arm carbon nanotubes.
[0025] As a further solution, the current collector includes a current collector containing metal. The current collector containing metal in the present invention includes not only metal current collectors but also composite current collectors.
[0026] The present invention also provides a negative electrode sheet, a positive electrode sheet or a separator having the lithium composite layer. The lithium composite layer in the present invention is particularly suitable for use in a negative electrode sheet to form a lithium composite negative electrode. The lithium composite layer is beneficial to inhibiting the generation of lithium dendrites in the negative electrode, thereby improving the safety performance and electrical performance of the battery; when the lithium composite layer is used in a positive electrode sheet, it can not only be used as a lithium supplement material, but also inhibit the volume expansion of the positive electrode sheet; when the lithium composite layer is used in a separator, it is beneficial to reduce the volume expansion of the battery and improve the ion conduction rate.
[0027] The present invention also provides a method for preparing the negative electrode sheet of the composite layer, the method comprising:
[0028] Preparation of lithium-philic coating slurry: lithium-philic material and carbon material are subjected to low-temperature chemical reduction to obtain lithium-philic nanocomposite material, and then a binder is added and mixed evenly; preparation of porous resin layer slurry: conductive agent, binder, and trialdehyde resin are mixed evenly; lithium-philic coating slurry, porous resin layer slurry, and composite metal lithium layer are sequentially coated on the side close to the current collector. In the present invention, the mixing method can be selected by a person skilled in the art in the art in different ways, as long as the effect of uniform dispersion can be achieved. In the present invention, the coating method of the current collector includes single-sided coating and double-sided coating.
[0029] As a further solution, the conditions for the low-temperature chemical reduction are: temperature of 60°C-120°C, and reaction time of 2h-48h.
[0030] As a further solution, the preparation method further includes drying after coating the lithium-philic coating slurry and drying after coating the porous resin layer slurry. The drying temperature is usually 60°C-120°C, and those skilled in the art can adjust it according to actual conditions.
[0031] As a further solution, the coating method of the lithium-philic coating is selected from one or more of transfer coating, extrusion coating, gravure coating, micro-concave coating, and spray coating.
[0032] As a further solution, the coating method of the porous resin layer is selected from one or more of transfer coating, extrusion coating, gravure coating, micro-concave coating, and spray coating.
[0033] As a further solution, the metal lithium layer is disposed on the porous resin layer in a manner selected from one or more of mechanical rolling, electrochemical deposition, and thermal evaporation. The selection of the metal lithium layer composite can be selected by those skilled in the art according to actual conditions.
[0034] The present invention also provides a negative electrode sheet, a positive electrode sheet or a separator having the lithium composite layer in a battery or a digital battery. The battery or the digital battery can be applied to 3C products, including but not limited to computers, tablet computers, mice, mobile phones, digital cameras, walkmans, electronic dictionaries, digital audio players, smart watches, MP3, MP4, radios, and Bluetooth headsets.
[0035] The present invention also provides an electrochemical device having a negative electrode sheet, a positive electrode sheet or a separator having the lithium composite layer. The electrochemical device can be used for terminal consumer products. The terminal consumer products applied for include but are not limited to mobile phones, notebook computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, and portable printers.
[0036] The present invention also provides an electrochemical device having a negative electrode sheet, a positive electrode sheet or a separator of the lithium composite layer, and the electrochemical device can be used for electrical equipment, including large electrical equipment and small electrical equipment, wherein small electrical equipment includes terminal consumer products, wearable electronic devices or movable electronic devices; large electrical equipment includes transportation electrical equipment. Transportation electrical equipment includes but is not limited to automobiles, motorcycles, power-assisted bicycles, buses, subways, high-speed railways, airplanes, and ships; wearable electronic devices or movable electronic devices include but are not limited to head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, drones, motors, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium ion capacitors.
[0037] As a further solution, the battery further includes a positive electrode, the positive electrode includes a positive electrode material, and the positive electrode material includes a lithium-containing positive electrode material and a lithium-free positive electrode material.
[0038] As a further solution, the lithium-containing positive electrode material includes one or more of lithium cobalt oxide, lithium iron phosphate, nickel-cobalt-manganese ternary, lithium-rich manganese base, lithium manganese oxide, and nickel-manganese spinel.
[0039] As a further solution, the lithium-free positive electrode material includes one or more of sulfur, sulfur-carbon composite materials, iron sulfide, titanium sulfide, and iron fluoride.
[0040] As a further solution, the battery includes one of a liquid battery, a solid-state hybrid battery, a semi-solid-state battery, and an all-solid-state battery.
[0041] The characteristics and beneficial effects of the present invention are:
[0042] (1) The lithium composite layer obtained by the present invention is directly compatible with the existing preparation process of the negative electrode sheet, positive electrode sheet or separator of the lithium ion battery. The lithium-philic nanocomposite material and the porous resin material can be realized by the coating process. The metal lithium layer can be composited by the rolling process. The lithium composite layer of the present invention is used for the negative electrode sheet, positive electrode sheet or separator. The obtained lithium composite negative electrode sheet, positive electrode sheet or separator can be produced in roll-to-roll manner, has good consistency, and can achieve low cost.
[0043] (2) The lithium composite layer of the present invention is particularly suitable for use in negative electrode sheets. Obtaining a lithium composite negative electrode can effectively alleviate the problems of large volume expansion, severe lithium dendrite growth, and many interface side reactions during the deposition and dissolution of metallic lithium; and the lithium composite negative electrode can achieve high mass energy density and high volume energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 Schematic diagram of the lithium composite negative electrode of the present invention.
[0046] Figure 2 The test results of the raw materials in the lithium composite negative electrode of the present invention are as follows: Figure 2 (a) is a photo of the raw material of the porous resin layer. Figure 2 (b) is a SEM image of the raw material in the porous resin layer. Figure 2 (c) is the XRD diffraction pattern of the silver-carbon composite material. Figure 2 (d) is the TEM image of the silver-carbon composite material.
[0047] Figure 3 The electrical performance result diagram of the battery provided by the embodiment of the present invention, wherein Figure 3 (a) is a cycle performance diagram provided by the embodiment, Figure 3 (b) is a capacity decay diagram provided in an embodiment. DETAILED DESCRIPTION
[0048] In order to facilitate understanding of a lithium composite layer of the present invention, the lithium composite layer of the present invention will be described more comprehensively below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.
[0049] In the present invention, the lithium composite layer used in the negative electrode sheet is taken as an example to further study the improvement effect of the lithium composite layer on the battery when used in the negative electrode sheet.
[0050] In the present invention, the same preparation method is used in Examples 1 to 5. The preparation method of the lithium composite negative electrode has the following steps:
[0051] Preparation of lithium-philic coating slurry: lithium-philic material and carbon material are subjected to low-temperature chemical reduction to obtain lithium-philic nanocomposite materials, wherein the conditions for low-temperature chemical reduction are a temperature of 100°C, a reaction time of 24h, and a mass ratio of carbon material to lithium-philic material of 100:1; then a binder is added, wherein PVDF is selected as the binder and mixed evenly, and the mass proportion of PVDF in the lithium-philic nanocoating slurry is 10%; preparation of porous resin layer slurry: conductive agent, binder, and trialdehyde resin are mixed evenly, wherein graphene is selected as the conductive agent and PVDF is selected as the binder, and the mass proportion of PVDF in the porous resin layer slurry is 10%, and the mass proportion of graphene in the porous resin layer slurry is 10%; lithium-philic coating slurry is coated on the current collector in sequence, dried at 80°C, coated with porous resin layer slurry, dried at 80°C, and composite metal lithium layer. The current collector is selected as metal copper
[0052] The coating method of the lithium-philic coating is selected from one or more of transfer coating, extrusion coating, gravure coating, micro-concave coating, and spray coating.
[0053] The coating method of the porous resin layer is selected from one or more of transfer coating, extrusion coating, gravure coating, micro-concave coating and spray coating.
[0054] The metal lithium layer is disposed on the porous resin layer by one or more of mechanical rolling and electrochemical deposition.
[0055] Comparative Examples 1 to 4 and Comparative Example 6 in the present invention are also obtained by the preparation method of the present invention.
[0056] The preparation method of the lithium-philic coating in comparative example 5 of the present invention adopts the preparation method described in the above-mentioned examples 1 to 5. The metal organic framework layer in comparative example 5 is grown in situ on the surface of the lithium-philic coating by a wet chemical method. A metal oxide thin layer is first formed on the surface of the lithium-philic coating by a pre-oxidation treatment, and then the oxide thin layer is etched by an etchant to generate a large amount of metal ions. The metal oxidant coordinates with the etchant, so that a uniform and dense MOF array layer is formed on the surface of the lithium-philic coating. The reaction time for in-situ growth is 30 hours, and the reaction temperature is 100°C. A thin ZnO layer is formed on the surface of the zinc layer by pre-oxidation treatment, and then ZnO is etched by 2-methylimidazole (HMIM) to generate a large amount of Zn 2+ , Zn 2+ The MOF array layer is formed uniformly on the surface of the galvanized copper foil by coordination with HMIM. The etching and coordination are called "in-situ growth". A metal lithium layer is then deposited on the metal organic framework layer by mechanical rolling or electrochemical deposition.
[0057] We also tested the expansion rate of the lithium composite negative electrode: the current density of discharge deposition was 1mA / cm 2The deposition capacity can be controlled by controlling the deposition time, where 2 mAh / cm 2 With 4mAh / cm 2 The deposition time corresponding to the deposition capacity is 2h and 4h respectively.
[0058] The lithium composite negative electrode of the present invention was used as the negative electrode and lithium cobalt oxide (LCO) was used as the positive electrode material, and the cycle performance and energy density of the battery were tested, and the voltage range of the test was 2.75V-4.6V.
[0059] Verification result analysis:
[0060] Table 1 Expansion rate results of lithium composite negative electrode plates of the embodiments and comparative examples
[0061]
[0062] We successfully obtained a lithium composite negative electrode through the preparation method of the present invention. We tested the expansion rate of the obtained lithium composite negative electrode, and the test results are shown in Table 1. We can see that the performance of the lithium composite negative electrode of Examples 1 to 5 of the present invention is better than that of Comparative Examples 1 to 6, and the expansion rate of the lithium composite negative electrode of the present invention is significantly reduced. We also used Example 1 of the present invention in a soft-pack battery, with the lithium composite negative electrode of the present invention as the negative electrode and lithium cobalt oxide (LCO) as the positive electrode material, and tested the electrical performance. The test results are shown in Table 1. Figure 3 As shown, we can Figure 3 It was found that the lithium composite negative electrode obtained in Example 1 has high cycle performance and energy density. Figure 3 In a, it can be found that the mass energy density of the battery measured in the first week of discharge exceeds 390Wh / Kg; Figure 3 In b, it can be seen that after the 50th cycle of the battery, the capacity retention rate of Example 1 is 76%, and the discharge capacity is 2.8Ah. It can be seen that the lithium composite negative electrode of the present invention can effectively alleviate the problems of large volume expansion, severe lithium dendrite growth, and many interface side reactions in the process of metal lithium deposition and dissolution; and the lithium composite negative electrode of the present invention can achieve high quality energy density and high volume energy density. We believe that it is mainly through the design of the lithium composite negative electrode of the present invention and the mutual coordination between the metal lithium layer, the porous resin layer and the lithium-philic coating that the stability and safety of the lithium negative electrode are significantly improved. We can also verify this by comparing Examples 1 to 5 with Comparative Examples 1 to 2. Figure 1It is shown in the figure that we designed a porous resin layer in the lithium composite negative electrode. The porous resin layer of the present invention is used as the main skeleton structure of the lithium composite negative electrode. The porous resin layer has a good ability to store metal lithium, which is conducive to the deposition of metal lithium from the negative electrode surface to the porous resin layer, thereby reducing the expansion rate of the negative electrode. On the other hand, the porous resin layer acts as a bridge between the metal lithium layer and the lithium-philic coating, forming a deposition channel for metal lithium, which promotes the deposition of metal lithium from the metal lithium layer to the lithium-philic coating. We also further set a lithium-philic coating under the porous resin layer. The lithium-philic coating can change the deposition order of metal lithium. The bottom lithium-philic coating can induce the metal lithium deposited in the porous resin layer to further begin to deposit toward the bottom of the lithium composite negative electrode. The lithium-philic coating and the porous resin layer cooperate with each other to further reduce the expansion rate of the negative electrode. In addition, the use of the lithium-philic coating can change the deposition morphology of metal lithium, induce uniform and dense deposition of metal lithium, and the uniform and dense deposition of metal lithium is conducive to reducing interface side reactions and improving the cycle stability of the battery. In order to improve the energy density of the negative electrode, we also designed a metal lithium layer on the surface of the porous resin layer. The metal lithium layer has good compatibility with the porous resin layer. We partially embed the metal lithium layer into the porous resin layer. On the one hand, it is beneficial for the metal lithium to smoothly pass through the porous resin layer and deposit downward. On the other hand, the thickness of the mutual embedding of the porous resin layer and the metal lithium layer can be adjusted to control the total thickness of the lithium composite negative electrode. The porous resin layer also has space for lithium deposition, which is beneficial to reduce the volume expansion of the negative electrode; in addition, the metal lithium mass ratio and volume ratio of the metal lithium layer in the lithium composite negative electrode can be increased, which is beneficial to improve the energy density of the battery. It can be seen that the present invention can promote the lithium composite negative electrode to obtain better stability and safety by designing the mutual coordination between the metal lithium layer, the porous resin layer and the lithium-philic coating. We also set a current collector below the lithium-philic coating, which is beneficial to improve the mechanical strength of the lithium composite negative electrode, so that the lithium composite negative electrode obtained by the present invention can be used in different types of batteries.
[0063] On this basis, we further preferred the lithium-philic materials in the lithium-philic coating and the raw materials in the porous resin layer. First, the lithium-philic materials in the lithium-philic coating need to promote the uniform and dense deposition of the metal lithium in the lithium composite negative electrode on the basis of lithium-philicity in order to reduce the interface side reactions; secondly, the selection of raw materials in the porous resin layer needs to have good compatibility with the metal lithium layer and the lithium-philic coating at the same time to form a stable lithium composite negative electrode; and the raw materials also need to have certain flexibility and elasticity, which is conducive to the embedding of the metal lithium layer; in addition, the raw materials of the porous resin layer need to have absorption capacity, and can cooperate well with the metal lithium layer, so as to promote the smooth downward deposition of the metal lithium on the surface of the metal lithium layer. We can find that by comparing Examples 1-5 with Comparative Examples 4-5, Examples 1-5 obtain the selection of raw materials in the lithium-philic coating and the porous resin layer in the lithium composite negative electrode, so that the lithium-philic coating, the porous resin layer and the metal lithium layer of the present invention form a good composite, thereby promoting the downward deposition of metal lithium, and significantly reducing the expansion rate of the lithium composite negative electrode.
[0064] On this basis, in the porous resin layer, the porosity, specific surface area, and pore size of the raw materials in the porous resin layer will further affect the absorbency of the porous resin layer, so that the porous resin layer can better cooperate with the metal lithium layer. On the one hand, it can stably compound with the metal lithium layer, and on the other hand, it can also absorb the metal lithium on the surface of the metal lithium layer to deposit downward. On this basis, we found that only by designing appropriate particle sizes of lithium-philic materials and carbon materials in the lithium-philic coating can the coordination between the lithium-philic coating and the porous resin layer be further improved. In the lithium-philic coating, the lithium-philic material is evenly dispersed and coated on the surface of the carbon material to form a lithium-philic nanocomposite material. When the particle size of the lithium-philic material and the carbon material is not suitable or the coating method is not suitable, it is easy to cause the lithium-philic material to be unable to be evenly coated on the surface of the carbon material, which directly affects the formed lithium-philic coating. On the one hand, it will lead to an increase in the thickness of the lithium-philic coating, affecting the thickness of the entire lithium composite negative electrode. On the other hand, because a uniform and flat lithium-philic coating cannot be formed, the balance between the absorption rate in the porous resin layer and the deposition rate on the lithium-philic coating will be broken, and the uniform and dense deposition mode of metal lithium will be destroyed, so that the expansion rate of the negative electrode will be significantly increased, which can be verified by comparing Examples 1 to 5 with Comparative Examples 3 and 6. It can be seen that the particle size of the lithium-philic material and the carbon material in the lithium-philic coating, the porosity, specific surface area, and pore size of the raw materials in the porous resin layer are further designed in the present invention, so as to promote the uniform deposition of metal lithium, thereby reducing the expansion rate of the lithium composite negative electrode.
[0065] On this basis, we compared Example 1 to Example 5 and found that the lithium composite negative electrode obtained in Example 3 has the smallest expansion rate. We believe that this is directly related to the selection of lithium-philic materials, lithium-philic material particle size, carbon material particle size in the lithium-philic coating, and the selection of trialdehyde resin, porosity, specific surface area, and pore size of the trialdehyde resin in the porous resin layer that matches it. We believe that silver can form an infinite solid solution with the deposited metallic lithium, which can better induce the deposition of metallic lithium, and the lithium-philic nanocomposite material formed by silver and carbon materials can better cooperate with the porous resin layer formed by the phenolic resin glue in the porous resin layer. On this basis, the particle size of silver particles and the particle size of carbon materials were further designed. The particle size of silver is 5nm, and the particle size of carbon material is 50nm, which can form a thinner, uniform and smooth lithium-philic coating; and the porosity of the phenolic resin glue is further designed to be 80%, and the specific surface area is 100m 2 / g, and the pore size is 30nm, which is conducive to the balance between the absorption rate in the porous resin layer and the deposition rate of metal lithium on the surface of the lithium-philic coating. In addition, phenolic resin glue has better absorption capacity, chemical stability, corrosion resistance, aging resistance, and heat resistance. In summary, we further prefer that the raw material in the porous resin layer is phenolic resin glue, the porosity of the phenolic resin glue is 70%-90%, and the specific surface area is 90m 2 / g-110m 2 / g, the pore size is 20nm-30nm, the lithium-philic material in the lithium-philic coating is silver, the particle size of silver is in the range of 4nm-6nm, and the particle size of the carbon material is in the range of 40nm-60nm.
[0066] We also obtained the raw materials in Example 1 for testing, such as Figure 2 As shown. Among them, Figure 2 (a) is the phenolic resin adhesive material in Example 1 of the present invention, Figure 2 (b) The phenolic resin glue material is evenly distributed in the porous resin layer, and the particle size distribution of the phenolic resin glue material is even, with an average particle size of 30μm-40μm. It can be seen that lithium deposition channels can be formed between the raw material particles. Figure 2 (c) is the XRD pattern of the silver-carbon composite material Ag@SP. The XRD diffraction spectrum shows that the main diffraction peak of the prepared nano-silver carbon material Ag@SP is consistent with the silver peak of PDF#-04-0783. Except for the diffraction peak at about 22.5° belonging to carbon, there is basically no impurity peak, which proves that the silver in the prepared nano-silver carbon material is a pure phase single silver material. Figure 2 The TEM test results in (d) show that the prepared nano-silver-carbon composite material is uniformly dispersed and coated in the nano-carbon material, and the particle size of the nano-silver is basically within 10 nm.
[0067] In summary, through the design of the present invention, the lithium composite negative electrode of the present invention can effectively alleviate the problems of large volume expansion, severe lithium dendrite growth, and many interface side reactions during the deposition and dissolution of metallic lithium; and the lithium composite negative electrode of the present invention can achieve high mass energy density and high volume energy density.
[0068] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium composite layer, characterized in that The lithium composite layer comprises a lithium-philic coating, a porous resin layer and a metal lithium layer which are sequentially arranged near the current collector side.
2. A lithium composite layer according to claim 1, characterized in that: The raw material of the porous resin layer includes trialdehyde resin, the porosity of the raw material is 60%-90%, and the specific surface area is 10m 2 / g-300m 2 / g, pore size is 1nm-500nm; Further preferably, the particle size of the raw material of the porous resin layer is in the range of 3 μm-100 μm; More preferably, the trialdehyde resin includes one or more of urea-formaldehyde resin glue, phenol-formaldehyde resin glue, and melamine resin glue.
3. A lithium composite layer according to claim 1, characterized in that: The lithium-philic coating is a composite material of a lithium-philic material and a carbon material; the raw materials of the lithium-philic coating include a lithium-philic material and a carbon material; the lithium-philic material is uniformly dispersed and coated on the surface of the carbon material; Further preferably, the mass ratio of the carbon material to the lithium-philic material is (10-1000):1; Further preferably, the particle size range of the carbon material is 10nm-500nm; the particle size range of the lithium-philic material is 1nm-10nm; Further preferably, the lithium-philic material includes one or more of silver, magnesium, and zinc, and the carbon material includes one or more of conductive carbon, acetylene black, graphene, single-arm carbon nanotubes, and multi-arm carbon nanotubes.
4. A lithium composite layer according to claim 1, characterized in that: The raw material of the porous resin layer includes phenolic resin glue, the porosity of the phenolic resin is 70%-90%, and the specific surface area is 90m 2 / g-110m 2 / g, the pore size is 20nm-30nm; the particle size range of the carbon material in the lithium-philic coating is 40nm-60nm; the lithium-philic material in the body-philic coating is silver, and the particle size range of the silver is 4nm-6nm.
5. A lithium composite layer according to claim 1, characterized in that: The thickness of the lithium-philic coating is 1 μm-10 μm, the thickness of the porous resin layer is 5 μm-200 μm, and the thickness of the metal lithium layer is 1 μm-200 μm.
6. A lithium composite layer according to claim 1, characterized in that: The raw materials of the lithium-philic coating layer also include a binder, and the raw materials of the porous resin layer also include a binder and a conductive agent; More preferably, the binder includes one or more of PVDF, aqueous dispersion of acrylonitrile multipolymer, PTFE, PAN, CMC, and SBR; Further preferably, the conductive agent includes one or more of conductive carbon, graphene, single-arm carbon nanotubes, and multi-arm carbon nanotubes; Further preferably, the mass proportion of the binder in the raw materials of the lithium-philic coating is 1%-40%; More preferably, the binder accounts for 1%-10% by mass in the raw materials of the porous resin layer; and the conductive agent accounts for 1%-10% by mass in the porous resin layer.
7. A negative electrode sheet, a positive electrode sheet or a separator comprising the lithium composite layer according to any one of claims 1 to 6.
8. A battery or electrochemical device comprising the negative electrode sheet, positive electrode sheet or separator according to claim 7.
9. The method for preparing a negative electrode sheet of a lithium composite layer according to claim 7, characterized in that: The preparation method comprises: preparing a lithium-philic coating slurry: obtaining a lithium-philic nanocomposite material by a low-temperature chemical reduction method for a lithium-philic material and a carbon material, and then adding a binder and mixing them uniformly; preparing a porous resin layer slurry: mixing a conductive agent, a binder and a trialdehyde resin uniformly; and sequentially coating the lithium-philic coating slurry, the porous resin layer slurry and the composite metal lithium layer on the side close to the current collector; Further preferably, the conditions for the low-temperature chemical reduction are: temperature of 60°C-120°C, reaction time of 2h-48h; Further preferably, the preparation method further comprises drying after coating the lithium-philic coating slurry, and drying after coating the porous resin layer slurry.
10. Use of the lithium composite layer according to any one of claims 1 to 6 in a negative electrode sheet, a positive electrode sheet, a separator, a battery or an electrochemical device.